HOW 60:40 POLICY AFFECTS THE DEVELOPMENT OF SCIENCE CURRICULUM IN MALAYSIA - Zainudin, Suhanna; Halim, Lilia Hali; Iksan, Zanaton (Proceeding 7th International Seminar on Regional Education, 2015)
Abstrak Since 1967, Malaysianâs Ministry of Education has constructed a policy called the 60:40 Policy. This Policy aims to enroll 60% of students into Science/Technical stream while the other 40% into Art streams. This policy is based on the 1967 Statement Report of Higher Education Planning Committee. Although the implementation of this 60:40 policy has been almost half a decade, targeted ratio was found to be very far from the desired goals. Among the factors that influence students not to choose the Science / Technical stream is due to their lack of interest in Science subjects, they also felt that Science is difficult and the circle of people donât encourage them enough to participate in the Science stream, caused by inadequate exposure to science-based careers. The involvement and achievement of students in rural areas are lower compared to those in urban area, which is caused by geographical factors and low socio-economic status. Ministry of Education (MOE) has taken initiatives to replace the Integrated Curriculum for Primary Schools (KBSR) to the Standard Curriculum for Primary Schools (KSSR) in 2011. But this transformation does not agree well with the 60:40 Policy because Science subjects have been replaced by the World Science and Technology. Other than that, the integration of Science, Technology, Engineering and Mathematics subjects (STEM) and 21st century learning is also seen as an approach that draws students interest to science. This approach must be integrated into the Science curriculum and consequently supporting the 60:40 policy. It is a hope that the 60:40 Policy can be realized by our countrys education system by the year 2020.Keywords: 60:40 Policy, STEM, KSSR and 21st Century Learning